A genomewide scan for quantitative trait loci underlying areal bone size variation in 451 Caucasian families - Shen, H (BMJ Group, 2006)
BACKGROUND: Bone size is an important determinant of bone strength and is under strong genetic control. OBJECTIVE: To identify quantitative trait loci (QTL) for areal bone size variation, a large‐scale genomewide linkage scan was carried out in 451 Caucasian families. PARTICIPANTS AND METHODS: Of 4124 people with phenotypes, 3899 were genotyped with 410 microsatellite markers. Multipoint linkage analyses were carried out in the entire sample, as well as in men and women separately. Potential epistatic interactions between identified genomic regions were also assessed. RESULTS: Several potentially important genomic regions were identified, such as 8q24 for hip bone size (logarithm of the ratio of the odds that two loci are linked (LOD) 3.27) and 2p24 (LOD 2.04) for spine bone size. 8q24 may also interact with 19p13 to affect hip bone size. Several sex‐specific QTL were also detected, such as 14q21 (LOD 2.94) for wrist bone size in women and 16q12 (LOD 2.19) for hip bone size in men. CONCLUSIONS: Together with previous findings, this study has further delineated the genetic basis of bone size and laid a foundation for future studies to eventually elucidate the mechanisms of bone size regulation and associated fracture risks.